Primary and post-primary infection with varicella-zoster virus in an atopic child. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Herpes zoster affects 1/5,000 children aged less than 5 (2), whereas in an outpatient clinic of pediatric dermatology its frequency is 0.4%. It is due to an endogenous reactivation of the virus in subjects with a history of previous varicella. An intrauterine or early -in the first 2 months- infection can be followed by precocious herpes zoster (1), occurring in the first year of age. In our case the child, in spite of his severe and exuding AD, had a mild varicella. Also herpes zoster, that affected our baby patient 3 years later when AD, although persistent, had got less severe, was mild. Moreover, also the concern regarding the vaccination with varicella-zoster virus in subjects with atopic dermatitis subsided with the clinical experience.